Evaluation of the p53 pathway in polycystic ovarian syndrome pathogenesis and apoptosis enhancement in human granulosa cells through transcriptome data analysis - M. Zanjirband; R. Hodayi; Z. Safaeinejad; M. H. Nasr-Esfahani; R. Ghaedi-Heydari (Scientific Reports, 2023)
Abstract The polycystic ovarian syndrome (PCOS) is closely associated with enhanced apoptosis of granulosa cells, which have a vital role in maturation of oocytes. p53 plays a critical role in the regulation of apoptosis and cell cycle arrest, metabolism and insulin resistance. The aim of this study was to investigate the impact of p53 pathway in enhancing apoptosis and abnormal function of granulosa cells. In this study, microarray analysis and RNA sequencing were downloaded from the GEO and used as datasets. Principal Component Analysis (PCA) and online SSizer tool were applied to evaluate the experiment quality control and sample sufficiency, respectively. Bioinformatics’ analyses were performed on the selected datasets, and validated by qRT-PCR and western blot analyses. Three datasets out of five ones were chosen for re-analyzing based on the PCA outcomes. 21 deregulated genes were identified via filters including p < 0.05 and |log2FC|≥ 1. Functional enrichment analysis confirmed the relevance of cell cycle regulation and apoptosis as common biological hallmarks in PCOS. Results have shown differentially expressed p53 target genes involved in apoptosis (BAX, FAS, PMAIP1, and CASP8), cell cycle (Cyclins, Cyclin dependent kinases), glucose metabolism and insulin resistance (THBS1), and p53 regulation (MDM2). Subsequently, the relative mRNA expression of FAS, PMAIP1 and MDM2 genes, and protein levels of p53 and MDM2 were confirmed using granulosa cells collected from 20 PCOS women and 18 control individuals by qRT-PCR and western blot, respectively. Results of this study represent the possible role of p53 pathway in pathogenesis of PCOS particularly, through the enhancement of apoptosis in granulosa cells.